2003
DOI: 10.2174/1568011033353443
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol and Cancer: Chemoprevention, Apoptosis, and Chemoimmunosensitizing Activities

Abstract: The polyphenolic compound Resveratrol is a naturally occurring phytochemical and can be found in many plant species, including grapes, peanuts and various herbs. Several studies have established that Resveratrol can exert anti-oxidant and anti-inflammatory activities. It also has activity in the regulation of multiple cellular events associated with carcinogenesis. This review describes the general properties of Resveratrol including its relationship to estrogen, its effect on lipid metabolism, its cardiovascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
94
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(97 citation statements)
references
References 66 publications
2
94
0
Order By: Relevance
“…Resveratrol is reported to exert antitumor activities at various stages of tumor initiation, promotion and progression (Jang et al, 1997). This is corroborated by reports of chemo-preventive effect of resveratrol in various cancer cell lines like, HeLa, A549 and MCF-7 (Cal et al, 2003). Various mechanisms for anti-proliferative action of resveratrol have been proposed including increase in tumor suppressor proteins like, p53, phosphorylation of Rb protein and transcription factors like NF-κB and AP-1 (Liu et al, 2010).…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Resveratrol is reported to exert antitumor activities at various stages of tumor initiation, promotion and progression (Jang et al, 1997). This is corroborated by reports of chemo-preventive effect of resveratrol in various cancer cell lines like, HeLa, A549 and MCF-7 (Cal et al, 2003). Various mechanisms for anti-proliferative action of resveratrol have been proposed including increase in tumor suppressor proteins like, p53, phosphorylation of Rb protein and transcription factors like NF-κB and AP-1 (Liu et al, 2010).…”
Section: Introductionmentioning
confidence: 68%
“…Resveratrol is a parent compound of a family of molecules including glucosides and polymers (Cal et al, 2003), existing in cis and transconfigurations in narrow range of spermatophytes of which vines, peanuts and pines are the prime representatives (Kiselev et al, 2011;Nakata et al, 2012;Neves et al, 2012). Previous studies have reported that resveratrol exerted antitumor activities at various stages of tumor initiation, promotion and progression (Cimino et al, 2012;Stefanska et al, 2012;Whitlock et al, 2012), including in esophageal squamous cell carcinoma (Tang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…They include protection against cardiovascular disease, ischemia, osteoporosis, cancer, and aging by means of mechanisms that include removal of reactive oxygen species, inhibition of mitosis and inflammation, and estrogen mimicry (1)(2)(3)(4)(5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…Despite extensive investigation, no clear molecular basis for the actions of resveratrol has emerged. A variety of hypotheses have been proposed to explain its functions: antioxidant effects, proapoptotic effects, cell-cycle regulation, inhibition of protein kinases, regulation of NFκB and Iκ3, and modulation of estrogen effects (3,6). As a polyphenol, resveratrol will evidently exhibit reductive properties and consequently will scavenge reactive oxygen species (ROS, such as H 2 O 2 , HO·, and 0 2− ) (7).…”
mentioning
confidence: 99%